Phytohormones Signaling Mechanisms and Crosstalk in Plant Development and Stress Responses - El-Esawi, Mohamed (IntechOpen, 2017)
Phytohormones are regulatory compounds that play crucial roles in plants. This book brings together recent work and progress that has recently been made in the dynamic field of phytohormone regulation in plant development and stress responses. It also provides new insights and sheds new light regarding the exciting hormonal cross talk phenomenon in plants. This book will provoke interest in many readers and scientists, who can find this information useful for the advancement of their research works.